Brasil versus ALCA na estratégia das negociações: aço, alumínio e cobre - Silva, Cristiane Ayres da (2006)
This paper aims to study some Brazilian issues that involve the formation of the Free Trade Area of the Americas (FTAA), mainly focusing on the analysis of the Brazilian industry of steel, aluminum and copper with respect to protectionist matters. Firstly, the study shows the Theory of International Trade developed from the ideas of David Ricardo, demonstrating the current tendency of commercial and financial globalization, followed by the presentation of some existing economic blocks. Subsequently, the Brazilian external politics strategies in order to overcome the impact of the proposals that involve the FTAA s creation, including within the WTO s scope, will be studied. Brazilian industry s competitiveness of the above-mentioned sectors will be analyzed as well, emphasizing the North-American tariff and non-tariff issues involved in the Brazil-USA trade